Assessment approaches and methods in physiotherapy education: A scoping review protocol - Katie L. Kowalski; Andrews Tawiah; Erin Miller; Maren Goodman; Greg Alcock; Heather Gillis (PLoS ONE, 2025)
Introduction Assessment in physiotherapy education is essential to ensuring graduates meet professional standards, demonstrate competence and are prepared to provide high-quality, patient-centered care. Assessment approaches (principles guiding assessment design, sequence and implementation) and methods (techniques used to evaluate performance) should be constructively aligned with curriculum content and learning outcomes, and assess the breadth of competencies required for practice. While individual studies describe assessment approaches and methods in physiotherapy education, there is no comprehensive synthesis or strategic analysis of their strengths, weaknesses, opportunities and threats. Objectives To 1) identify and characterize assessment approaches and methods used in physiotherapy education; 2) analyze the strengths, weaknesses, opportunities and threats of assessment approaches and methods used in physiotherapy education. Methods This scoping review will follow Joanna Briggs Institute guidance and report according to Preferred Reporting Items for Systematic review and Meta-analysis extensions for Protocols and Scoping Reviews. The protocol is registered with Open Science Framework. Searches will be performed in Medline, CINAHL, EMBASE, ProQuest Education Research Index, Scopus, PsycINFO, and relevant grey literature from inception until July 23, 2025. Eligible studies will report primary research on assessment approaches or methods in the academic curriculum of university-based clinical physiotherapy education programs. Studies focusing only on clinical education, reviews, opinion pieces will be excluded. Two reviewers will independently screen studies and extract data using a standardized tool. A narrative synthesis will characterize assessment approaches and methods, categorizing approaches by guiding principles and methods by type. Methods will be mapped to Miller’s pyramid of clinical competence. A directed content analysis will identify the strengths, weaknesses, opportunities and threats influencing assessments in physiotherapy education. Conclusion This review will provide a comprehensive synthesis and strategic analysis of assessments in physiotherapy education. Findings will inform evidence-based assessment practices that support optimal student learning, experiences and readiness for contemporary practice.